PERBANDINGAN GEL EKSTRAK TEMU KUNCI DAN TRIAMSINOLON ASETONID TERHADAP PENYEMBUHAN STOMATITIS AFTOSA REKUREN - Alviani Tiku Rante; Shanty Chairani; Tyas Hestiningsih (Jurnal Kesehatan Gigi dan Mulut (JKGM), 2019)
Recurrent apthous stomatitis (RAS) is a condition with painful recurrent ulcer in the oral mucosa. Manytherapeutic options in the treatment of RAS indicate there is no definitive therapy. The aim of this study was todetermine the effect of fingerroot extract gel on healing of RAS by measuring ulcer size and pain level of RAS.This experimental study used pretest-posttest control group design consisted on 38 female students of DentistryStudy Program Medical Faculty of Sriwijaya University with minor RAS. Sample were divided into 2 groups andinstructed to apply the fingerroot gel (treatment group) or triamcinolone acetonide (control group) 3 times a dayfor 7 days. Ulcer size was measured by using a dental probe and pain level was evaluated by visual analog scale(VAS) at the initial day (day-0), day-3, day-5, and day-7. The results showed that ulcer size and pain level inboth groups at day-3 lower than day-0, size decreased on day-5, and eliminated completely on day-7, while thepain had disappeared on day-5. No significant difference in size between the two groups at day-3, but at day-5ulcer size in triamcinolone acetonide group was smaller significantly than fingerroot group (p<0.05). There wasno significant difference of pain level between the two groups. Fingerroot have efficacy for reducing size andpain level of the RAS lesion so it can be used as an alternative in the treatment of RAS.